2013
DOI: 10.1108/yc-01-2013-00340
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual differences between adolescent and adult impulse buyers

Abstract: Purpose -There have been recent calls for research into the impulse shopping behaviours of adolescent consumers -an important topic because adolescents are: an increasingly important market segment; a segment which has recently been empowered by the availability of easy credit; and which is increasingly targeted by strategic marketing collateral. This paper responds to the call by aiming to focus on the impulse shopping behaviours of adolescents.Design/methodology/approach -The research is qualitative in natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 167 publications
(168 reference statements)
0
21
0
3
Order By: Relevance
“…Van Campenhout (2015) cites Webley’s (2005, p. 194) finding that children show significant progress in their understanding of economics when they are between 6 and 12 years of age. There is a discernible difference between the financial attitudes and behaviours of youth consumers relative to adult consumers, with Brici et al (2013) finding adults to be more aware of financial constraints and budgets than youth. Adults and youth were also found to associate different emotions with impulse spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Van Campenhout (2015) cites Webley’s (2005, p. 194) finding that children show significant progress in their understanding of economics when they are between 6 and 12 years of age. There is a discernible difference between the financial attitudes and behaviours of youth consumers relative to adult consumers, with Brici et al (2013) finding adults to be more aware of financial constraints and budgets than youth. Adults and youth were also found to associate different emotions with impulse spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in both groups has its merits. It has produced important insights into the conditions and factors affecting teenagers’ consumption choices (Lee, 2016; Perera et al , 2016), revealed incongruences between attitudes toward sustainable consumption and respective practices (Hume, 2010; Hitchings et al , 2013; Francis and Davis, 2015) and allowed the analysis of distinct, often problematic tendencies like impulsive shopping (Brici et al , 2013) or compulsive consumption (Xu, 2008) among teenagers. However, research from both fields has largely failed to provide a sophisticated foundation of what should be analyzed as teenagers’ SCBs.…”
Section: Introductionmentioning
confidence: 99%
“…When designing the stores, retailers may consider the factors such as young and adults characteristics that motivate the impulse buying. It is evident that adults understand their situation even during the impulse buying when compared to young consumers (Brici et al, 2013).…”
Section: Impulse Buyingmentioning
confidence: 99%